2016
DOI: 10.4315/0362-028x.jfp-16-155
|View full text |Cite
|
Sign up to set email alerts
|

Modeling the Effect of Temperature and Water Activity on the Thermal Resistance of Salmonella Enteritidis PT 30 in Wheat Flour

Abstract: Salmonella continues to be a problem associated with low-moisture foods, particularly given enhanced thermal resistance at lower water activity (a). However, there is a scarcity of thermal inactivation models accounting for the effect of a. The objective of this study was to test multiple secondary models for the effect of product (wheat flour) a on Salmonella enterica Enteritidis phage type 30 thermal resistance. A full-factorial experimental design included three temperatures (75, 80, and 85°C) and four a va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 76 publications
(30 citation statements)
references
References 17 publications
6
23
0
1
Order By: Relevance
“…For the postfabrication results, the same general rank ordering was true (P , 0.05), except for a smaller difference between almond and wheat products. This observation is consistent with prior Salmonella Enteritidis PT 30 studies, which have reported larger D-values for high fat products (e.g., D 838C of 16 min for peanut butter (16) compared with a D 808C of 5 min for wheat flour (22)).…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…For the postfabrication results, the same general rank ordering was true (P , 0.05), except for a smaller difference between almond and wheat products. This observation is consistent with prior Salmonella Enteritidis PT 30 studies, which have reported larger D-values for high fat products (e.g., D 838C of 16 min for peanut butter (16) compared with a D 808C of 5 min for wheat flour (22)).…”
Section: Resultssupporting
confidence: 91%
“…According to Smith et al (22), Salmonella Enteritidis PT 30, which was inoculated via a method similar to the present postfabrication protocol, exhibited a D 808C of 5.5 min in wheat flour at 0.43 a w , which was lower than that for postinoculation wheat flour at 0.4 a w (15.1 min). Smith et al (22) used commercial white wheat flour, which may have altered the heat resistance because of differences in composition (i.e., lower lipids content) and particle-cell interactions. Syamaladevi et al (24) also assessed thermal inactivation of a Salmonella cocktail in wheat flour at 808C (inoculated postfabrication).…”
Section: Resultsmentioning
confidence: 99%
“…The z values of SiO 2 -Salmonella, SiO 2 -E. faecium, and NFMP-Salmonella in NFMP at a w = 0.25 ± 0.02 varied from 16.0 to 16.5°C. These data match previously reported z values of Salmonella Enteritidis (16.9°C) and E. faecium (16.2°C) in wheat flour at a w = 0.30 ± 0.02 (Liu et al, 2018) and those of Salmonella Enteritidis in wheat flour (16.7 ± 0.73°C) modeled from D-values at 75 to 85°C at a w = 0.31-0.70 (Smith et al, 2016). From reported data, z values of both strain sets might be independent of inert carriers (NFMP or SiO 2 ) and food matrices.…”
Section: Effect Of Dry Carriers On Bacterial Survivability and Thermasupporting
confidence: 90%
“…Smith et al reported D values of 9.97, 5.51, and 2.11 min at 75, 80, and 85°C for Salmonella enterica Enteritidis PT 30 in wheat flour (a w , 0.43). They also reported ␦ values of 8.08, 4.97, and 1.59 min for the same temperatures (48). In another study, a D 80 value of 6.9 min for Salmonella in all-purpose wheat flour with a w of 0.45 was reported (49).…”
Section: Resultsmentioning
confidence: 80%
“…In the present study, the EHEC's D, ␦, and Z values were smaller than those previously reported for Salmonella, but they were still considerably higher than those for E. coli in many other types of matrices, including foods with higher a w . A closed system using 0.5-ml PCR tubes was applied for thermal treatment procedures preventing changes in a w decrease during the process, which may inversely affect the thermal death kinetics calculations (48,49).…”
Section: Resultsmentioning
confidence: 99%